Purification and identification of Angiotensin-I Converting Enzyme (ACE) inhibitory peptide from lizard fish (Saurida elongata) hydrolysate. (March 2015) - Wu, Shanguang; Feng, Xuezhen; Lan, Xiongdiao; Xu, Yuanjin; Liao, Dankui
Highlights: In current study, Lizard fish ( Saurida elongata ) muscle protein was hydrolyzed by neutral protease to obtain the hydrolysate with angiotensin-I converting enzyme (ACE) inhibitory activity. A novel ACE inhibitory peptide with the sequence of Arg-Val-Cys-Leu-Pro (RVCLP) was isolated by multi-step isolation, including ultrafiltration, size exclusion chromatography, ion exchange and HPLC and showed high ACE-inhibitory activity. ACE inhibitory peptide RVCLP was purified from Lizard fish hydrolysate by multi-step isolation and showed high ACE-inhibitory activity. Abstract: Lizard fish ( Saurida elongata ) muscle protein was hydrolyzed by neutral protease to obtain the hydrolysate with angiotensin-I converting enzyme (ACE) inhibitory activity. A novel ACE inhibitory peptide was successfully purified from Lizard fish protein hydrolysate (LFPH) by ultrafiltration, size exclusion chromatography, and high-performance liquid chromatography (HPLC). The amino acid sequence of the purified peptide was identified as Arg-Val-Cys-Leu-Pro (RVCLP) and in vitro ACE inhibitory activity assay revealed an IC50 value of 175 µM. Our study suggests that peptide from lizard fish hydrolysate may be beneficial as antihypertensive compounds for use as functional food ingredients or pharmaceuticals against hypertension.